2022
DOI: 10.29333/ejmste/12443
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of student’s perception learning calculus with GeoGebra and cycle model

Abstract: Learners in the 21st century need technological support in the learning process because of the advancements made in technology for teaching and learning. A GeoGebra-oriented classroom uses one of these technologies that can be implemented in the classroom. The new developed cycle model implemented in the study and explored the effect of using GeoGebra mathematical software on students' perceptions to using GeoGebra software to learn calculus. A mixed research methodology was employed. In the quantitative part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
1
0
0
Order By: Relevance
“…The results above are consistent with those of other research that has looked at the impact of a technologically advanced classroom on students' ability to learn (Bedada & Machaba, 2022;Shadaan & Leong, 2013). Since there was a clear improvement, the GeoGebra software could be used as a tool to help teach and learn calculus, especially the study of derivatives of functions.…”
Section: Discussionsupporting
confidence: 90%
“…The results above are consistent with those of other research that has looked at the impact of a technologically advanced classroom on students' ability to learn (Bedada & Machaba, 2022;Shadaan & Leong, 2013). Since there was a clear improvement, the GeoGebra software could be used as a tool to help teach and learn calculus, especially the study of derivatives of functions.…”
Section: Discussionsupporting
confidence: 90%
“…7. Bedada & Machaba (2022) The usage of GeoGebra for studying differential calculus was seen favourably by the students, and they were happy with the choices made for the study's GeoGebra lesson-oriented course. 8.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study show that most users hold favourable views of GeoGebra and find it an effective pedagogical tool. Most researchers found that users have positive perspectives and perceptions about using GeoGebra (Owusu et al, 2023;Saralar-Aras, 2022;Bedada & Machaba, 2022;Handayani et al, 2022;Manganyana et al, 2020;Rafi & Sabrina, 2019;Machromah et al, 2019;Belgheis & Kamalludeen, 2018). Users believe that this software can enhance their understanding of mathematics concepts and increase their motivation and performance in learning mathematics.…”
Section: Discussionmentioning
confidence: 99%